Tolerância de porta enxertos cítricos ao alumínio em solução - Sbrissa, Mirella (Universidade Federal de São Carlos, 2013)
One of the main causes of losses in agricultural productivity is due to the high concentrations of aluminum (Al) in the soil solution, characteristic of acidic weathered soils in the humid tropical zone. Al affects the morphology and physiology of the root system, limiting the deepening of roots in the soil and the absorption of water and nutrients. The aim of this study was to evaluate the effect of different concentrations of Al (0; 7.5 mg L-1; 15 mg L-1; 22.5 mg L-1 and 30 mg L-1) on the root development of varieties of citrus rootstock Tangerine Sunki (Citrus sunki Hort. ex Tan.), Citrumelo Swingle (Citrus paradisi Macf. X Poncirus trifoliata Raf.) and Limoeiro Cravo (Citrus limonia Osbeck), through the evaluation of morphological changes in the roots of the seedlings visible by optical microscopy, the accumulation of dry biomass and the rate of root elongation. The experiment was carried out under laboratory conditions, in a completely randomized design, with six replications. The results of root growth rate (mm day-1) were subjected to analysis of variance and compared by the Tukey test (p<0.05). The increase in the concentration of Al in solution caused a decrease in the rate of root elongation (mm day-1) of the three rootstocks. The Limoeiro Cravo seedlings were less sensitive to the presence of Al regarding to biomass accumulation. The presence of Al did not affect the accumulation of biomass in the stem of Citrumelo Swingle seedlings, but reduced the accumulation of root biomass in the Tangerine Sunki seedlings. The 30-day period of exposure of roots to Al was not enough to promote visible morphological changes. The critical concentration of Al in solution, from which there was a decrease in the accumulation of biomass and in the rate of root elongation, was 15 mg L-1 of Al. The root biometry indicated the following sequence of rootstocks tolerancy to Al in solution: Citrumelo Swingle = Limoeiro Cravo > Mandarin Sunki.
Tolerance of citrus rootstocks to aluminum in solution
Keywords: fitotoxidez; alumínio; Citrumelo Swingle; Mandarin Sunki.; Limoeiro Cravo; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO